Systemic therapy in stage IV pancreatic cancer: a population-based analysis using the National Cancer Data Base - Nabin Khanal (Therapeutic Advances in Medical Oncology, 2015)
Background: Pancreatic cancer accounts for approximately 7% of all cancer deaths. More than half of all pancreatic cancers are stage IV at diagnosis, where systemic chemotherapy is used with the goal of life prolongation as well as palliation. The patient characteristics and health system factors that drive the use of systemic therapy are unknown. Method: This is a retrospective study of stage IV pancreatic cancer patients ( n = 140,210) diagnosed between 2000 and 2011 in the NCDB. NCDB contains approximately 70% of new cancer diagnosis from more than 1500 accredited cancer programs in the United States and Puerto Rico. Chi-squared test was used to determine any differences in characteristics of patients who did or did not receive systemic therapy. Results: Our study demonstrated that only 49.1% of stage IV pancreatic cancer patients received systemic therapy. The use of systemic therapy is significantly lower in female, African American/Hispanic, patients older than 40 years, those without insurance or with Medicare and Medicaid, higher Charlson Comorbidity Score, poor economic and educational status and in nonacademic centers. Conclusions: This is the largest study to evaluate the determinants of systemic therapy use in stage IV pancreatic cancer. The use of systemic therapy was significantly lower in patients older than 40 years, lower educational status, nonprivate insurance and with higher Charlson Comorbidity Scores. In addition, the use of systemic therapy was lower with female sex, African Americans/Hispanic, and lower socio-economic status. Understanding the barriers in the use of systemic therapy as well as appropriate utilization of systemic therapy can both optimize cancer care.